De Blau a Riobaldo: a estratégia de narração como legado - Fabricio, Valéria de Castro (2018)
This research consists of a comparative analysis between narrative structures of the works Contos Gauchescos, by Simões Lopes Neto and Grande Sertão: veredas, by João Guimarães Rosa. Our work is based on the principle that Simões Lopes Neto aimed to rescue, register and perpetuate, through his text, important aspects of the regional legacy sul-rio-grandense. For this,he elaborated a strategy of differentiated narration in Contos Gauchescos, which operates through the interaction of four resources: the opening note, the establishment of a regional narrator profile, the option of dialogue and the insertion of a young interlocutor. We understand that such a model was absorbed by Guimarães Rosa in Grande Sertão: veredas and innovated by him. This projection of actions that includes the creation of a model, it's subsequent influence on another, culminating in it's re-creation and renewal, we call the process of: fixation, meditation and innovation. To identify it, we start with the intent of critical assessments of regionalism with the intent of defining and updating it. Subsequently, we examined the production contexts of two works, aiming to identify their field of influence. Finally, to compare the two structures of narration, we adopt as a theoretical support the essay by Walter Benjamin The narrator considers the work of Nikolai Leskov intending the profiling of the model of narrator and the postulates of Dal Farra about the narrator in first person and it's ideological character. From the benjaminian study, we selected three categories for the approximation of the narrators Blau Nunes and Riobaldo: memory, loquacity and advice. Subsequently, we adopt the postulates of Genette on hypertextuality to select criteria for comparison, specifically: transposition and forging. After such surveys, we compared the narrative structures of the two works based on their similarities, aiming at first to identify them and later to recognize how the process of re-creation and innovation was operated.